ROBB: recurrent proximal policy optimization reinforcement learning for optimal block formation in bitcoin blockchain network - Dutta, Amit (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Science in Computer Science, 2023.